Antibacterial Activity Test of Staphylococcus aureus from Henna Leaf Extract (Lawsonia inermis Linn) - Laily Nurliana; Halimatussaddiyah Ritonga; Fatmawati; Rustam Musta (Universitas Pendidikan Mandalika, 2026)
An antibacterial activity test against Staphylococcus aureus using henna leaf extract (Lawsonia inermis Linn.) has been conducted. This study aimed to determine the secondary metabolite components and the major compounds present in the henna leaf extract, as well as its inhibitory activity against Staphylococcus aureus. The secondary metabolite components were identified through phytochemical screening, while the major compounds were determined using GC-MS. The antibacterial activity was tested at concentration variations of 75%, 50%, 25%, and 12.5%. The resulting inhibition zones were then categorized according to standard criteria. The significance of the effect of concentration on the inhibition zones was analyzed using a one-way ANOVA test, followed by LSD test at α = 0.05. The results showed that the henna leaf extract tested positive for flavonoids, alkaloids, tannins, and quinones and GC-MS analysis shows compounds included 1,5-heptadiene-3,4-diol, 2-methyl-; 2-undecene, 2-methyl-; cyclotrisiloxane, hexamethyl-; 2,6-dihydroxyacetophenone; and 2,3-dihydroxybenzoic acid. The antibacterial activity test results showed that different concentrations (12.5%, 25%, 50%, and 75%) produced different inhibition zones; however, all were still classified within the same category, namely moderate. Statistical analysis indicates a significant effect of concentration on the inhibitory activity against the test bacteria, where F test = 4.771 > F crit = 4.066 at α = 0.05. Further analysis using the LSD test revealed two groups with significantly different inhibitory effects: the 75% and 50% concentration groups showed significantly higher inhibitory activity compared to the 25% and 12.5% groups.